Current and potential uses of bioactive molecules from marine processing waste. (30th September 2015) - Suleria, Hafiz Ansar Rasul; Masci, Paul; Gobe, Glenda; Osborne, Simone
Abstract: Food industries produce huge amounts of processing waste that are often disposed of incurring expenses and impacting upon the environment. For these and other reasons, food processing waste streams, in particular marine processing waste streams, are gaining popularity amongst pharmaceutical, cosmetic and nutraceutical industries as sources of bioactive molecules. In the last 30 years, there has been a gradual increase in processed marine products with a concomitant increase in waste streams that include viscera, heads, skins, fins, bones, trimmings and shellfish waste. In 2010, these waste streams equated to approximately 24 million tonnes of mostly unused resources. Marine processing waste streams not only represent an abundant resource, they are also enriched with structurally diverse molecules that possess a broad panel of bioactivities including anti‐oxidant, anti‐coagulant, anti‐thrombotic, anti‐cancer and immune‐stimulatory activities. Retrieval and characterisation of bioactive molecules from marine processing waste also contributes valuable information to the vast field of marine natural product discovery. This review summarises the current use of bioactive molecules from marine processing waste in different products and industries. Moreover, this review summarises new research into processing waste streams and the potential for adoption by industries in the creation of new products containing marine processing waste bioactives. © 2015 Society of Chemical Industry